OCEANFILMS‐2: Representing coadsorption of saccharides in marine films and potential impacts on modeled marine aerosol chemistry - Susannah M. Burrows; Eric Gobrogge; Li Fu; Katie Link; Scott M. Elliott; Hongfei Wang; Rob Walker (Geophysical Research Letters)
Abstract Here we show that the addition of chemical interactions between soluble monosaccharides and an insoluble lipid surfactant monolayer improves agreement of modeled sea spray chemistry with observed marine aerosol chemistry. In particular, the alkane:hydroxyl mass ratio in modeled sea spray organic matter is reduced from a median of 2.73 to a range of 0.41–0.69, reducing the discrepancy with previous Fourier transform infrared spectroscopy (FTIR) observations of clean marine aerosol (ratio: 0.24–0.38). The overall organic fraction of submicron sea spray also increases, allowing organic mass fractions in the range 0.5–0.7 for submicron sea spray particles over highly active phytoplankton blooms. Sum frequency generation experiments support the modeling approach by demonstrating that soluble monosaccharides can strongly adsorb to a lipid monolayer likely via Coulomb interactions under appropriate conditions. These laboratory findings motivate further research to determine the relevance of coadsorption mechanisms for real‐world, sea spray aerosol production.